Large-scale structure formation in ionic solution and its role in electrolysis and conductivity - Yee, Chut-Ngeow; Ooi, Chong Heng Raymond; Tan, Luck Pheng; Misran, Misni; Tang, Nyiak Tao (Public Library of Science, 2019)
That water may not be an inert medium was indicated by the presence at water’s interfaces a negatively charged solute free zone of several hundred microns in thickness called the exclusion zone (EZ). Further evidence was demonstrated by Ovchinnikova’s experiments (2009) showing that water can store and release substantial amount of charge. We demonstrate that the charge storage capacity of water arises from highly stable large-scale ionic structures with measurable charge imbalances and discrete levels of charge density. We also show evidence that the charge zones formation requires ionic solutes, and their formation correlate to large change in conductivity, by as much as 250%. Our experiments indicate that large-scale structuring plays a pivotal role in electrolysis and conductivity in ionic solution. We propose that water is an electrochemically active medium and present a new model of electrolysis and conductivity in ionic solution. © 2019 Yee et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.